Respuesta :
Answer:
The initial value problem [tex]y(x) = 4 e^{-2x} -3 e^{6 x}[/tex]
Step-by-step explanation:
Step1:-
a) Given second order homogenous constant co-efficient equation
[tex]y^{ll} - 4y^{l}-12y=0[/tex]
Given equation in the operator form is [tex](D^{2} -4D-12)y=0[/tex]
Step 2:-
b) Let f(D) = [tex](D^{2} -4D-12)y[/tex]
Then the auxiliary equation is [tex](m^{2} -4m-12)=0[/tex]
Find the factors of the auxiliary equation is
[tex]m^{2} -6m+2m-12=0[/tex]
m(m-6) + 2(m-6) =0
m+2 =0 and m-6=0
m=-2 and m=6
The roots are real and different
The general solution [tex]y = c_{1} e^{-m_{1} x} + c_{2} e^{m_{2} x}[/tex]
the roots are [tex]m_{1} = -2 and m_{2} = 6[/tex]
The general solution of given differential equation is
[tex]y = c_{1} e^{-2x} + c_{2} e^{6 x}[/tex]
Step 3:-
C) Given initial conditions are y(0) =1 and y1 (0) =-26
The general solution of given differential equation is
[tex]y(x) = c_{1} e^{-2x} + c_{2} e^{6 x}[/tex] .....(1)
substitute x =0 and y(0) =1
[tex]y(0) = c_{1} e^{0} + c_{2} e^{0}[/tex]
[tex]1 = c_{1} + c_{2}[/tex] .........(2)
Differentiating equation (1) with respective to 'x'
[tex]y^l(x) = -2c_{1} e^{-2x} + 6c_{2} e^{6 x}[/tex]
substitute x= o and y1 (0) =-26
[tex]-26 = -2c_{1} e^{0} + 6c_{2} e^{0}[/tex]
[tex]-2c_{1} + 6c_{2} = -26[/tex] .............(3)
solving (2) and (3) by using substitution method
[tex]substitute c_{2} =1- c_{1}[/tex] in equation (3)
[tex]-2c_{1} + 6(1-c_{1}) = -26[/tex]
on simplification , we get
[tex]-2c_{1} + 6(1)-6c_{1}) = -26[/tex]
[tex]-8c_{1} = -32[/tex]
dividing by'8' we get [tex]c_{1} =4[/tex]
substitute [tex]c_{1} =4[/tex] in equation [tex]1 = c_{1} + c_{2}[/tex]
so [tex]c_{2} = 1-4 = -3[/tex]
now substitute [tex]c_{1} =4 and c_{2} =-3[/tex] in general solution
[tex]y(x) = c_{1} e^{-2x} + c_{2} e^{6 x}[/tex]
[tex]y(x) = 4 e^{-2x} -3 e^{6 x}[/tex]
now the initial value problem
[tex]y(x) = 4 e^{-2x} -3 e^{6 x}[/tex]